Exploring the Dynamic and Spillover Effects of Renewable Energy, Energy Consumption, and Financial Growth on SDG 13: Evidence from India and China - Çağatay, Bilge; Demirkale, Özge (International Journal of Energy Economics and Policy, 2025)
Climate change represents a critical global challenge, propelled by increasing greenhouse gas emissions, industrial growth, and reliance on fossil fuels. The United Nations’ Sustainable Development Goal (SDG) 13 underscores the imperative for immediate climate action and sustainable energy policies. This study seeks to analyze the influence of energy consumption, renewable energy transition, and financial development in India and China on climate change mitigation, in accordance with Sustainable Development Goal (SDG) 13. The energy policies and financial mechanisms of the two largest emerging economies and carbon emitters are pivotal to global sustainability. The primary research question of this study is, how do India’s and China’s energy sectors and financial development influence climate change mitigation efforts? The findings reveal that despite advancements in renewable energy, both nations continue to struggle with high carbon emissions and environmental degradation. China’s substantial investments in clean energy and financial instruments, including green bonds, have facilitated emission reductions, while India encounters infrastructural and financial limitations despite its ambitious sustainability objectives. The study underscores the necessity of integrating financial development with sustainable energy initiatives to reduce environmental harm. By evaluating the environmental consequences of energy policies, this research contributes to the broader discourse on sustainability and the role of major economies in global climate mitigation efforts.